POLYGAMY IN INDONESIA AND ITS RELEVANCE TO THE PROTECTION OF WOMEN AND CHILDREN IN THE PERSPECTIVE OF ISLAMIC LAW PHILOSOPHY - Dri Santoso; Muhamad Nasrudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
This article discusses the regulation of polygamy in Law No. 1 of 1974 and its derivative rules, as well as the Compilation of Islamic Law with an analysis of Islamic legal philosophy/maqashid al-shari’ah. This research is based on the legitimacy of polygamy as stated in Law Number 1 of 1974 concerning Marriage, article 3, paragraph 2. Polygamy also has rules that require the husband to obtain formal permission from the wife through a court process. Why do the Marriage Regulations regulate this? This research is based on a qualitative descriptive literature review. The method of analysis employed was content analysis, which involved creating an inventory of Indonesian family law norms and analyzing them using the maqashid al-shari’ah theory. This study finds that the regulation of polygamy in Indonesia is carried out to protect women's rights and children's rights. Furthermore, the rule aims to build a happy, peaceful, and prosperous family in the long run (sakinah, mawaddah, wa rahmah). This is in accordance with maqashid al-shari’ah, particularly in terms of soul preservation and descendent preservation.